The Effect of Brand Equity on Consumer Loyalty through Consumer Satisfaction as an Intervening Variable in Taro Food MSMEs in Bogor City - Widia Alma Hanifi; Dwi Gemina; Endang Silaningsih (Eduvest - Journal of Universal Studies, 2025)
This study investigates the influence of brand equity on consumer loyalty through consumer satisfaction as an intervening variable in Taro food MSMEs in Bogor City. The research highlights the significant role of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's economic development, particularly in enhancing consumer loyalty through effective branding strategies. The methodology employs a quantitative approach, utilizing surveys distributed to 172 respondents to gather data on brand equity, consumer satisfaction, and loyalty. The findings reveal that brand equity positively impacts consumer satisfaction, which in turn significantly influences consumer loyalty. This research provides insights for MSME actors to improve their branding strategies, enhancing consumer engagement and loyalty in a competitive market.